2012
DOI: 10.1089/neu.2011.2233
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Progressive Hemorrhagic Injury after Traumatic Brain Injury: Derivation and Validation of a Risk Score Based on Admission Characteristics

Abstract: Previous studies have demonstrated that patients with traumatic brain injury (TBI) who also have progressive hemorrhagic injury (PHI), have a higher risk of clinical deterioration and worse outcomes than do TBI patients without PHI. Therefore, the early prediction of PHI occurrence is useful to evaluate the status of patients with TBI and to improve outcomes. The objective of this study was to develop and validate a prognostic model that uses information available at admission to determine the likelihood of PH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 20 publications
2
85
1
Order By: Relevance
“…Prior reports have identified that radiographic factors such as the presence of a subdural hematoma (SDH) [4, 6, 12], subarachnoid hemorrhage (SAH) [4, 5, 7], and larger contusion volume [5, 6, 10] are associated with higher risk for HPC, as well as clinical factors such as older age [4, 13], hyperglycemia [14], antiplatelet medication use [15], low platelet count [16], and timing of the initial CT scan [4, 7]. One prior group attempted to develop a predictive score using clinical parameters [14]; but the lowest risk patient group still had a high incidence of HPC (10.3 %) in this study, and the algorithm was complex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior reports have identified that radiographic factors such as the presence of a subdural hematoma (SDH) [4, 6, 12], subarachnoid hemorrhage (SAH) [4, 5, 7], and larger contusion volume [5, 6, 10] are associated with higher risk for HPC, as well as clinical factors such as older age [4, 13], hyperglycemia [14], antiplatelet medication use [15], low platelet count [16], and timing of the initial CT scan [4, 7]. One prior group attempted to develop a predictive score using clinical parameters [14]; but the lowest risk patient group still had a high incidence of HPC (10.3 %) in this study, and the algorithm was complex.…”
Section: Introductionmentioning
confidence: 99%
“…One prior group attempted to develop a predictive score using clinical parameters [14]; but the lowest risk patient group still had a high incidence of HPC (10.3 %) in this study, and the algorithm was complex.…”
Section: Introductionmentioning
confidence: 99%
“…Significant heterogeneity was present in this meta-analysis due to several factors. 11 Prospective observation study GCS <13 and positive head CT scan Joseph et al 12 Retrospective cohort Any GCS level and positive head CT scan Juratli et al 13 Prospective observation study Any GCS level and positive head CT scan Yuan et al 14 Retrospective cohort Any GCS level and positive head CT scan Allard et al 15 Subgroup post hoc analysis of RCT for hypertonic resuscitation for TBI GCS 8 positive head CT scan White et al 16 Prospective cohort Any GCS level and positive head CT scan Yadav et al 17 Prospective cohort Any GCS level and positive head CT scan Kaups et al 18 Retrospective cohort Severe TBI (AIS > 3) Sanus et al 19 Retrospective cohort Any GCS level and positive head CT scan Oertel et al 20 Retrospective cohort Any GCS level and positive head CT scan Stein et al 21 Retrospective cohort GCS < 13 Stein et al 22 Retrospective cohort GCS < 13 TBI, traumatic brain injury; GCS, Glasgow Coma Score; CT, computed tomography; RCT, randomised control trial. There was some variation in the size of the studies (range 46-540); however, the meta-analysis was not heavily weighted by one particular study.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true after surgical intervention for another ICH, where surgical decompression can reduce adja cent mass effect (and associated tamponade of hemorrhage), allowing a parenchymal contusion to enlarge or "blossom" Some patients are more susceptible to rebleeding, also called progressive hemorrhagic injury (PHI), and these patients may warrant closer postoperative monitoring or imaging. 13 A list of risk factors for rebleeding/PHI follows:…”
Section: Parenchymal Hematomasmentioning
confidence: 99%